2014
DOI: 10.1097/qai.0000000000000279
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Pregnancy After Antiretroviral Therapy Initiation and Associated Factors in 8 West African Countries

Abstract: Introduction This study aimed at estimating the incidence of pregnancy after antiretroviral therapy (ART) initiation in eight West African countries over a 10-year period. Methods A retrospective analysis was conducted within the international database of the IeDEA West Africa Collaboration. All HIV-infected women aged <50 years and starting ART for their own health between 1998 and 2011 were eligible. Pregnancy after ART initiation was the main outcome and was based on clinical reporting. Poisson regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 22 publications
2
13
3
Order By: Relevance
“…This study from Johannesburg, South Africa found that pregnancy incidence increased among women on ART when their CD4 count was >100 cells/mm 3 and with better adherence . The finding of this study is consistent with two others that found pregnancy incidence to be significantly higher among women who started ART at WHO Stage 1/2 rather than WHO Stage 3/4 .…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…This study from Johannesburg, South Africa found that pregnancy incidence increased among women on ART when their CD4 count was >100 cells/mm 3 and with better adherence . The finding of this study is consistent with two others that found pregnancy incidence to be significantly higher among women who started ART at WHO Stage 1/2 rather than WHO Stage 3/4 .…”
Section: Resultssupporting
confidence: 89%
“…One study from rural Uganda found that pregnancy incidence peaked 12–18 months after initiation , while another study from rural Uganda found peaks at 6–12 months and then again at 4 years, presumably due to a birth interval effect . In West Africa, data from ART clinics in six countries showed the highest pregnancy incidence in year four . In contrast, a study from Johannesburg, South Africa found no difference in pregnancy incidence by time on ART .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This decreasing incidence rate is in contrast to a recent study of HIV positive women in Uganda, aged15-49, which showed an increase in pregnancy rates from 29.8 to 122 per 1000 woman years between 2006 and 2010[26]. This study, and others[27][28][29][30], have shown increased pregnancy incidence with engagement in care and/or initiation of ART. In women of reproductive age who are not adolescents, this may be a positive trend, demonstrating better control of HIV and ability to conceive.…”
contrasting
confidence: 94%